Laser-scanning rangefinder fixed on a gimbal with two degrees of freedom - V. A. Zelenskiy; M. V. Kapalin (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2021)
A laser-scanning rangefinder mounted on a gimbal with two degrees of freedom is presented. The rangefinder can be used as part of a navigation system of an unmanned aerial vehicle to avoid obstacles or prevent collisions. Compared to stereo cameras, the device requires significantly less computing resources and is less dependent on lighting conditions. Compared to integrated lidars, the cost of the device is by an order lower. А model of the device was developed and an obstacle avoidance flight was simulated in the Gazebo simulator. The PX4/Avoidance software was used as an autopilot. As a result of a model experiment, we found that a scanning laser rangefinder can provide autonomous navigation with obstacle avoidance.